Public exposure in the Orenburg region due to natural sources of ionizing radiation. Part 2: Doses to the population of the eastern districts of the Orenburg region - T. A. Kormanovskaya; I. K. Romanovich; N. E. Vyaltsina; S. V. Gaevoy; D. V. Kononenko; K. A. Saprykin; E. S. Kokoulina; N. A. Koroleva (Радиационная гигиена)
The paper presents the estimated doses to the population of six eastern districts of the Orenburg region, Russia, based on the results of a comprehensive radiation survey conducted in 2019 in 34 settlements with previously found elevated levels of activity concentration of natural radionuclides in tap water from groundwater sources of drinking water supply. It is shown that the average individual annual effective dose due to all natural sources of ionizing radiation in 18 of 34 settlements corresponds to ‘elevated level’ of exposure due to natural sources according to established classification (from 5 to 10 mSv/year), and in another 7 settlements to ‘high level’ (over 10 mSv/year) with radon being the main contributor to the dose. Four settlements of Kvarkensky and Adamovsky districts, where the highest indoor radon concentrations had been found, were selected for a detailed survey, which included measurements of density of radon flux from the soil, radon concentration in soil gas, activity concentration of natural radionuclides in samples of building materials and in soil samples, and activity concentration of radon in tap water from groundwater sources of drinking water supply. Results of the detailed survey proved that the main source of radon in the buildings was the soil gas infiltration; compared to it, the contribution of waterborne radon release was insignificant.